PENGEMBANGAN ALAT EVALUASI PEMBELAJARAN AKUNTANSI VIRTUAL BERBASIS EDMODO - Fania Riski Felani; Joni Susilowibowo (Jurnal Pendidikan Ilmu Sosial, 2021)
The purpose of this research is to develop a virtual-based evaluation tool, namely by testing the feasibility of an evaluation tool in the form of Edmodo which is judged by several experts including media experts, evaluation experts and material experts. Where this research was tested by 2 expert lecturers and 1 accounting teacher. This research refers to the 4d model research which includes the stages of define, design, develop, and disseminate. The results of the Edmodo evaluation assessment from the experts showed an average percentage of success of 86.87% by getting the "very feasible" criteria and the data obtained were processed using a Likert scale. With the Edmodo evaluation tool, it can help in the learning process, both in terms of accuracy, accuracy and time and speed effectiveness. Therefore, this research is very suitable as a support in the learning process, especially as a learning evaluation tool for students with various learning groups.